The Apparent Diffusion Coefficient of Diffusion-Weighted Whole-Body Magnetic Resonance Imaging Affects the Survival of Multiple Myeloma Independently - Zhang, Bei; Bian, Bingyang; Zhang, Yanjiao; Zhang, Li; Zhang, Rongkui; Wang, Jiping (Frontiers in Oncology, 2022)
Background: Diffusion weighted whole-body MRI (DW-MRI) is increasingly used to evaluate bone diseases of multiple myeloma (MM), but there is lack of quantitative indicator for DW-MRI to reflect the prognosis of MM. Apparent diffusion coefficient (ADC) value in DW-MRI has potential correlations with some indexes of MM, but the influence of ADC on MM survival needs to be further verified. Methods: A total of 381 newly diagnosed MM patients were enrolled in the study to analyze the effect of ADC value in DW-MRI on progression free survival (PFS) and overall survival (OS). The Kaplan–Meier method was used to perform univariate survival analysis and Cox proportional hazards model was used for multivariate analysis. In addition to ADC value, genetic and serological indexes were also included. Results: The survivals were observed in univariate ADC stratification with median PFS of 52.0, 45.0, 34.0 and 26.0 months (the unit of ADC value was 10-3 mm2/s; the ADC ranges were ADC＜0.4886, 0.4886≤ ADC＜0.6545, 0.6545≤ ADC＜0.7750, and ADC ≥0.7750; 95% CI, 43.759-62.241, 46.336-53.664, 39.753-46.247 and 27.812-32.188). The OS were 81.0, 61.0, 47.0 and 36.0 months (p＜0.001; 95% CI, 71.356-82.644, 67.630-70.370, 57.031-60.969 and 36.107-43.893). In Cox proportional hazards model, ADC value was considered to be an independent risk factor affecting PFS and OS of MM (both p＜0.001). Conclusions: This study supports that ADC in DW-MRI may independently stratify MM patients and better predict their prognosis. The combined use of DW-MRI and other parameters allows more accurate evaluation of MM survival.